Pengaruh Pendidikan Kesehatan melalui Media Klik KB terhadap Minat Akseptor KB IUD pada Masa Pandemi - Is Susiloningtyas; Machfudloh Machfudloh; Adisa Dyah Witantri (Faletehan Health Journal, 2024)
COVID-19 pandemic impacted on family planning drop-outs and an increase in pregnancies. The use of intrauterine contraceptive device (IUD) is 99.4% effective in controlling the population; however, public interest in IUDs is low. This low interest can be overcome by providing education using Klik KB application. This research aimed to determine the impact of health education through Klik KB on the interest of IUD acceptors during the pandemic. The research type was quasi-experimental with a one-group pretest posttest design. The research was conducted from December to March 2022 with the population of 311 people and the sample of 31 people. The sampling technique was purposive sampling with inclusion and exclusion criteria. The data collection was carried out by distributing a questionnaire and providing an intervention. The data analysis used a frequency distribution table and Wilcoxon test. The research results showed that before providing health education using Klik KB, the majority of the respondents had moderate interest and after providing health education, the respondents’ interest became high. Providing health education using Klik KB application media has an influence on the acceptor’s interest on IUD at Pemalang District Health Center with a p value of 0.000. Midwives and National Population and Family Planning Board (Ina. BKKBN) are required to carry out more comprehensive outreach to the public using Klik KB application media.